Ecoeffectiveness as a strategy to achieve Sustainable development: an analysis based on the Cradle to Cradle paradigm (Dissertare, 2019)
Globally, the indiscriminate use of natural resources persists, deteriorating our environment (MA). The response to this situation has been oriented to the ecological practices of reducing, reusing and recycling, which only underuse the waste generated. It is necessary to evaluate the production and consumption systems to move towards sustainability. In 2015, the United Nations approved the 2030 Agenda that includes 17 Sustainable Development Goals (SDGs), whose fulfillment favors economic development and protects the MA for our generation and future ones. The present investigation, under a mostly quantitative approach, analyzes eco-effectiveness as a strategy for compliance with the SDGs, adopting the “Cradle to Cradle” (C2C) paradigm as a reference. For this purpose, correspondence was established between the goals set within these objectives and the quality criteria of the C2C. The study is descriptive, supported by documentary review, as a data collection technique, which are processed using frequency analysis. Of the 169 SDG goals, 66 (39%) correspond to the quality criteria mentioned. Of this total number of goals consistent with the C2C criteria, 90.90% is related to the Social Responsibility-Diversity criteria, while the link with the remaining criteria ranges between 39% and 50%. In order to achieve eco-effectivity under the C2C paradigm, the actions of Reconceptualizing, Redesigning and Reevaluating products, services and systems are proposed to subsequently: Reduce, Reuse and Recycle. It is concluded that Ecoeffectiveness is an applicable strategy in support of the SDGs.
Keywords: sustainable development; 2030 Agenda; Cradle to Cradle; ecoeffectiveness